Wntless spatially regulates bone development through β‐catenin–dependent and independent mechanisms. Issue 10 (21st August 2015) - Zhong, Zhendong A.; Zahatnansky, Juraj; Snider, John; Van Wieren, Emily; Diegel, Cassandra R.; Williams, Bart O.
<x xml:space="preserve">Abstract</x> Background : Canonical and noncanonical Wnt signaling pathways both play pivotal roles in bone development. Wntless/GPR177 is a chaperone protein that is required for secretion of all Wnt ligands. We previously showed that deletion of Wntless within mature osteoblasts severely impaired postnatal bone homeostasis. Results: In this study, we systemically evaluated how deletion of Wntless in different stages of osteochondral differentiation affected embryonic bone development, by crossing Wntless (Wls)‐flox/flox mice with strains expressing cre recombinase behind the following promoters: Osteocalcin, Collagen 2a1, or Dermo1. Ex vivo µCT and whole‐mount skeletal staining were performed to examine skeletal mineralization. Histology and immunohistochemistry were used to evaluate cellular differentiation and alterations in Wnt signaling. In this work, we found that Wntless regulated chondrogenesis and osteogenesis through both canonical and noncanonical Wnt signaling. Conclusions: These findings provide more insight into the requirements of different Wnt‐secretion cell types critical for skeletal development. Developmental Dynamics 244:1347–1355, 2015. © 2015 Wiley Periodicals, Inc.